Size distribution of atmospheric particulates and particulate-bound polycyclic aromatic hydrocarbons and characteristics of PAHs during haze period in Lampang Province, Northern Thailand - Phoothiwut, Sawan; Junyapoon, Suwannee (My University, 2013)
Size distributions of atmospheric particulates and particulate-bound polycyclic aromatic hydrocarbons (p-PAHs) in different inhalable fractions (9.0-5.8, 5.8-4.7, 4.7-3.3, 3.3-2.1, 2.1-1.1, 1.1-0.7, 0.7-0.4, and <0.4 μm) were investigated during a haze period in Lampang Province, Northern Thailand. The particulate samples were collected using an eight-stage cascade impactor. The sample filter in each stage was weighed to determine concentration followed by ultrasonic extraction with acetonitrile and then analysis using selected ion monitoring-gas chromatograph-mass spectrophotometer to identify 16 PAHs. Similarly, smoke emission from burning rice straw in the rice field and air sample during non-burning period were also analyzed. In this study, the particle size fractions were classified into three different size ranges according to their mechanism of formation: ultrafine particles (nuclei mode, d ae < 0.4 μm), fine particles (accumulation mode, 0.4 μm < d ae < 2.1 μm) and coarse particles (d ae > 2.1 μm). Experimental results show that the average concentration of particulate matter less than 10 μm during the haze period was 3.5 times higher than that during the non-burning period. The atmospheric aerosols during the haze period contained the largest fraction of particles in nuclei mode while the emission during rice straw burning introduced the largest fraction of particles in accumulation mode. The size distributions of total PAHs during the haze period and rice straw burning were shifted towards the smaller particles relative to their particle size distribution. The size distributions of total PAHs were bimodal during the haze period and unimodal during rice straw burning. The fractions of five- and six-ring PAHs bound on the particles were predominantly detected during the haze period whilst those of three- and four-ring PAH compounds were mainly found in smoke emitted from rice straw burning. The ratio of carcinogenic and noncarcinogenic PAH compounds during the haze period was composed of more carcinogenic PAHs than that during rice straw burning. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Haze period; Particulate-bound polycyclic aromatic hydrocarbons (p-PAHs); Rice straw burning; Size distribution